2019
DOI: 10.3390/life9040079
|View full text |Cite
|
Sign up to set email alerts
|

Nitrates as a Potential N Supply for Microbial Ecosystems in a Hyperarid Mars Analog System

Abstract: Nitrate is common in Mars sediments owing to long-term atmospheric photolysis, oxidation, and potentially, impact shock heating. The Atacama Desert in Chile, which is the driest region on Earth and rich in nitrate deposits, is used as a Mars analog in this study to explore the potential effects of high nitrate levels on growth of extremophilic ecosystems. Seven study sites sampled across an aridity gradient in the Atacama Desert were categorized into 3 clusters—hyperarid, middle, and arid sites—as defined by e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(57 citation statements)
references
References 101 publications
(154 reference statements)
5
52
0
Order By: Relevance
“…For this study, five sites were sampled on a latitudinal gradient from 22°S to 28°S (Figure 2). This sampling strategy was selected to provide an aridity gradient from hyperarid in the north to arid in the south (Figure 3); the sites are María Elena South (MES, 1,493 m altitude) (Azua‐Bustos, Caro‐Lara, & Vicuna, 2015), Point of No Return Dos (PONR‐2, 1,493 m altitude), Yungay (1,007 m altitude), Transition Zone 4 (TZ‐4, 1,658 m altitude), and Transition Zone 5 (TZ‐5, 588 m altitude), with 0–23 mm average annual precipitation estimated by Shen et al (2019) shown in Table 1. We note that visual small plant vegetation appeared in TZ‐4 and TZ‐5, and dried grass roots appeared in their soil samples (Figure 3b).…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…For this study, five sites were sampled on a latitudinal gradient from 22°S to 28°S (Figure 2). This sampling strategy was selected to provide an aridity gradient from hyperarid in the north to arid in the south (Figure 3); the sites are María Elena South (MES, 1,493 m altitude) (Azua‐Bustos, Caro‐Lara, & Vicuna, 2015), Point of No Return Dos (PONR‐2, 1,493 m altitude), Yungay (1,007 m altitude), Transition Zone 4 (TZ‐4, 1,658 m altitude), and Transition Zone 5 (TZ‐5, 588 m altitude), with 0–23 mm average annual precipitation estimated by Shen et al (2019) shown in Table 1. We note that visual small plant vegetation appeared in TZ‐4 and TZ‐5, and dried grass roots appeared in their soil samples (Figure 3b).…”
Section: Methodsmentioning
confidence: 88%
“…Similarly, we recently postulated that bulk N concentrations, largely supplied as nitrate by atmospheric deposition (Ewing et al, 2007;Michalski et al, 2004), could be diluted by higher sedimentation rates and thus more limited to microorganisms (Shen et al, 2019).…”
Section: Phosphorus Distribution and Microbial P Cycling In Atacamamentioning
confidence: 96%
See 2 more Smart Citations
“…Environmental variables such as elevation, pH, electrical conductivity, salt concentrations, total organic carbon (TOC) and total organic nitrogen (TON) were reported in Shen et al (2019). δ 13 C of TOC and δ 15 N of TON were determined together with TOC and TON by Elemental Analyzer-Isotope Ratio Mass Spectrometry (EA-IRMS) (Shen et al, 2019). Concentrations of microbial P extracted using the sequential soil phosphate extraction method (Tamburini et al, 2018) were reported in Shen et al (2020b).…”
Section: Environmental Variables and Principal Component Analysismentioning
confidence: 99%